First evidence of SO2-releasing bags controlling fungal growth, aflatoxins and cyclopiazonic acid contamination in unshelled peanuts - Cervini, Carla; Verma, Vaibhav; Verheecke-Vaessen, Carol; Medina, Angel; Magan, Naresh (Oxford University Press (OUP), 2026)
Peanuts (also known as groundnuts; Arachis hypogaea L.) are a globally significant cash crop but are highly susceptible to fungal contamination, particularly by Aspergillus section Flavi, which can contaminate the product with mycotoxins, including aflatoxins. This contamination poses serious food safety concerns, especially in low- and middle-income countries, limiting access to international markets. This study assessed the efficacy of slow-release SO2-bags compared to plastic bags (control) in reducing fungal growth and mycotoxin contamination in stored unshelled peanuts. Naturally contaminated and Aspergillus flavus-inoculated peanuts were stored at water activity (aw) levels of 0.85 and 0.95 for 15 days at 25°C. Fungal populations were monitored, aflatoxins and cyclopiazonic acid were analysed using LC-MS/MS qTRAP. SO2-releasing bags completely inhibited fungal growth in naturally contaminated peanuts and significantly reduced A. flavus population with effectiveness dependent on water activity. Additionally, SO2-releasing bags suppressed mycotoxin production. This study demonstrates, for the first time, the effectiveness of SO2-releasing bags in preventing fungal spoilage and mycotoxin contamination in post-harvest peanuts, offering a promising solution for enhancing peanut safety and quality.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; Microbiology; 3009 Veterinary sciences; 3107 Microbiology; 3207 Medical microbiology; groundnuts; mycotoxins; Aspergillus flavus; applied mycology